Hematology and Blood Chemistry Status of Most Frequently Consumed Ruminants in Community - Silvana Tana; Tyas Rini Saraswati; Enny Yusuf Yuniwarti (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2018)
Hematological and chemical status of blood in livestock can be used to diagnose the disruption of the hematologic system as well as help to diagnose many organ and systemic diseases. This study aimed to determine the hematology and blood chemistry status of various types of most frequently consumed ruminants in community. Types of ruminants used were cattle, goats and buffaloes. The research design was Completely Randomized Design (RAL) with 3 treatments on 3 types of male ruminants at slaughter age. Each treatment consisted of 3 times repetition. The animals used came from slaughterhouses in Kudus (cattle and buffaloes) and Semarang (goats). Observations of hematology and blood chemistry parameters were conducted on blood samples taken in the morning (at 03.00 a.m.). The parameters measured were the number of erythrocytes, hemoglobin (Hb) content, number of leukocyte and blood chemistry consisted of HDL and LDL cholesterol. The data obtained were analyzed by ANOVA and followed by Duncan test. The results showed that the highest number of erythrocytes and hemoglobin content was found in goats, whereas the highest LDL content was found in cattle. It can be concluded that goat has the best hematological status compared to cattle and buffalo.